PENGARUH IONOSFER PADA AKURASI PENENTUAN POSISI ABSOLUT DENGAN GPS SINGLE FREQUENCY PADA SAAT TERJADI BADAI MATAHARI - Buldan Muslim (Lembaga Penerbangan dan Antariksa Nasional, 2011)
The effect of the ionosphere on the propagation of signals emitted from GPS satellites at an altitude of about 20,000 km is in the form of code delay or carrier advance of the signal propagation time which depends on the Total Electron Content (TEC) and the GPS signals frequency. Coronal Mass Ejections (CMEs) occurred during October 28 and 29, 2003 solar storms have caused ionosphere disturbances called ionospheric storms. The ionospheric storms have degraded the accuration of single frequency GPS absolute positioning to more than 400%. Mitigation of ionospheric storms effect on the single frequency GPS absolute positioning by using Klobuchar model can not produce a significant increase in accuracy. Hence during the ionospheric storms, the regional ionospheric TEC model is needed for ionospheric correction of single frequency GPS absolute point positioning. Keywords: Solar storm, Ionosphere, Radio wave, Propagation, Positioning, Accuration